KONSEP PENDIDIKAN ANAK DALAM Al-QURâAN SURAT LUQMAN - Hamim, Khairul (LP2M IAIN Mataram, 2013)
Child represent beautiful grant from above which given by Allah SWT to human being to be educated and instructed in order to become good child âshaleh and shalehahâ. In Islam the parents is obliged to give correct education to their child as according to al-Qurâan, but education concept of child up to now have not yet become serious attention, even though in Islam academician and also parents itself. Through study of library research with contents analysis, that concept child education stated in Qs. Luqman is first, the obligation to give education of tauhid; second, obligation to have good behavior to parents; third, obligation to have religious service by shalat; fourth, obligation to dakwah in Allah SWT rules by good informing and prohibit to do badness; and fifth, always patient and not arrogant in attitude also in saying word